2015
DOI: 10.1353/lib.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

A Pluralistic Approach to the Philosophy of Classification

Abstract: Any classification system should be evaluated with respect to a variety of philosophical and practical concerns. This paper explores several distinct issues: the nature of a work, the value of a statement, the contribution of information science to philosophy, the nature of hierarchy, ethical evaluation, pre-versus postcoordination, the lived experience of librarians, and formalization versus natural language. It evaluates a particular approach to classification in terms of each of these but draws general less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A classification that is useful but somewhat less supportive of diversity might then better achieve social justice. Any classification must be judged in terms of a broad array of both philosophical and practical considerations (see Szostak 2015). It is thus worth noting that the sort of classification (and thesaurus) urged here has many further advantages.…”
Section: Advantages Beyond Social Diversitymentioning
confidence: 99%
“…A classification that is useful but somewhat less supportive of diversity might then better achieve social justice. Any classification must be judged in terms of a broad array of both philosophical and practical considerations (see Szostak 2015). It is thus worth noting that the sort of classification (and thesaurus) urged here has many further advantages.…”
Section: Advantages Beyond Social Diversitymentioning
confidence: 99%
“…He stresses throughout that a work is primarily defined by the ideas it conveys. I have suggested that “ideas” comprise some set of: descriptions of phenomena or relationships, causal arguments, theories applied, methods applied, and perspectives applied (Szostak 2014). Both Smiraglia and I appreciate that the subject matter of any work cannot be separated from its semantic content.…”
Section: The Nature Of a Workmentioning
confidence: 99%